2016
DOI: 10.1016/j.anpedi.2015.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Los errores de tratamiento en una unidad neonatal, uno de los principales acontecimientos adversos

Abstract: It is essential to determine the current state of ME, in order to establish preventive measures and, together with teamwork and good practices, promote a climate of safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
2
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 27 publications
2
6
2
3
Order By: Relevance
“…Most of the incidents analyzed in the present study were related to the medication, totaling 61.1% of the notifications. In a study recently published, the researchers found in a neonatal unit 511 reports of adverse drug-related events over a seven-year period, resulting in an incidence of 32.2 drug-related adverse events per 1000 days, with 39.5% of prescription errors, 68.1% of administration errors and 0.6% were adverse drug reaction 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Most of the incidents analyzed in the present study were related to the medication, totaling 61.1% of the notifications. In a study recently published, the researchers found in a neonatal unit 511 reports of adverse drug-related events over a seven-year period, resulting in an incidence of 32.2 drug-related adverse events per 1000 days, with 39.5% of prescription errors, 68.1% of administration errors and 0.6% were adverse drug reaction 19 .…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that the probability of permanent sequels and deaths of patients in the Neonatal Intensive Care Unit (NICU), caused by adverse events, is 0.6%. NICU can be characterized as a unit that receives patients less than 29 days old (10) .…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the USA, there are more than 30 suicidal attempts for each suicide death [10]. In Africa, the overall magnitude of suicide ranged from 2–3% [range 0.7–6.0%] [11, 13]. In Ethiopia, the prevalence of suicidal behaviors ranged from 0.9 to 60% [1416] for suicidal ideation, 3.8 to 27% [14, 17] for suicidal attempt, and 13.96% per 100,000 [18, 19] for completed suicide.…”
Section: Introductionmentioning
confidence: 99%
“…Factors such as psychiatric disorder [20], hopelessness, and substance use were also associated with completed suicide [1, 3, 5, 20]. Suicide is an emergency psychiatric problem [9, 20, 21] and need an urgent treatment; yet, stigma, taboo, laws, and other associated cultural criticism affect the societies’ attitude and practice toward the identification and treatment of suicidal behaviors [3, 5, 8, 9, 13, 21]. In spite of the high burden of suicidal behaviors, developing countries [11, 13] like Ethiopia give little research attention, and the available individual studies also reported inconsistent results, which need comprehensive up-to-date information.…”
Section: Introductionmentioning
confidence: 99%